Subterranean Reverberations and the Horror of the Chemical Sublime - Ektander, Caroline (Lagoonscapes)
This article examines how the faint, persistent hum of groundwater pumps exposes the limits of industrial clean-up. Focused on efforts to manage groundwater contaminated by a century of coal-based chemical industrialization in Bitterfeld-Wolfen, it draws on sonic methods and the concept of transmediation to explore how sound and water unsettle the illusion of containment. Attuning to these peripheral vibrations offers a way of sensing pollution as ongoing, relational, and irreducible – within what the paper frames as a toxic common.